1992
DOI: 10.1111/j.1530-0277.1992.tb00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism and the D2 Receptor Gene

Abstract: The allelic association of the human dopamine D2 receptor gene and alcoholism was evaluated in 20 male alcoholics and 20 controls (sex, race, and geographic place of birth matched). This study further examines the issue of alcoholism severity and A1 allele frequency. No difference in A1 allele frequency was observed between these two groups. Similarly, no relationship between alcoholism severity and A1 frequency within the alcoholics was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…This association has been supported in several, [2][3][4][5] but not all subsequent studies. [10][11][12][13] The A1 allele was also found to be associated with prolonged P300 latency, reduced visuospatial preference, and low cerebral glucose utilization, all putative markers of alcoholism and dopamine function deficiency. [15][16][17] In addition, the A1 allele has also been associated with substance abuse, [6][7][8][9] which led to its conceptualization as a 'reward gene'.…”
mentioning
confidence: 99%
“…This association has been supported in several, [2][3][4][5] but not all subsequent studies. [10][11][12][13] The A1 allele was also found to be associated with prolonged P300 latency, reduced visuospatial preference, and low cerebral glucose utilization, all putative markers of alcoholism and dopamine function deficiency. [15][16][17] In addition, the A1 allele has also been associated with substance abuse, [6][7][8][9] which led to its conceptualization as a 'reward gene'.…”
mentioning
confidence: 99%
“…After Blum et al [1990] reported that the frequency of TaqI A1 allele of DRD2 was higher in alcoholics than in nonalcoholic controls, several subsequent studies of other populations have replicated the finding Comings et al, 1991;Noble et al, 1991;Parsian et al, 1991;Amadeo et al, 1993;Neiswanger et al, 1995a]. However, many failed to do so [Bolos et al, 1990;Gelernter et al, 1991;Cook et al, 1992;Goldman et al, 1992;Turner et al, 1992;Arinami et al, 1993;Suarez et al, 1994;Sander et al, 1995;Lu et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…Since there is a wide variation in the allelic frequency of TaqI A1 of DRD2 among different populations [Barr and Kidd, 1993], one possibility is confounding by population admixture due to unmatched ethnicity between cases and controls [Gelernter et al, 1993;Pato et al, 1993]. The sample size of previous studies, such as Cook et al [1992] and Lu et al [1996], may not have sufficient power to detect the association. Some researchers have suggested that the association may exist exclusively among severe alcoholics Parsian et al, 1991;Arinami et al, 1993], and the prevalence of DRD2 A1 allele has been found to be higher in more severe alcoholics than in less severe ones Noble et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…Several case/control studies have investigated allelic variation in the TaqI A polymorphism but with controversial results. Several negative results were reported in comparisons of alcohol dependent and control individuals [Bolos et al, 1990;Gelernter et al, 1991;Cook et al, 1992;Turner et al, 1992;Arinami et al, 1993;Suarez et al, 1994] though many studies did obtain positive results for alcohol dependent individuals [Amadeo et al, 1993;Noble et al, 1994;Neiswanger et al, 1995] and for polysubstance abusers Lawford et al, 1997]. Averaging of A1 frequencies across 21 studies that included alcoholics and controls revealed greater frequency among alcoholics [Noble, 2003].…”
Section: Introductionmentioning
confidence: 99%